Scrolling into Learning: The Role of Digital Platforms in Enhancing English Language Skills among Students - Dida, Khareen (International Journal of Sustainability and Advanced Integrated Research, 2026)
The study examined the role of digital platforms in enhancing the English language skills of students. Using a descriptive quantitative research design, data were collected from 38 student respondents from Mountain Province, Philippines through a structured questionnaire. The study investigated how students’ engagement with digital platforms contributed to the development of vocabulary, reading comprehension, listening skills, and writing abilities. The results indicated that the majority of the respondents frequently used digital platforms that exposed them to English-language content. Findings showed that 81.6% of students reported vocabulary improvement, while 78.9% indicated enhanced reading and listening skills, and 71.1% experienced improvement in writing abilities through digital interaction. However, challenges such as distractions from non-academic content (63.2%) and internet connectivity issues (23.7%) were also identified. Overall, the study revealed that digital platforms served as valuable informal learning environments that supported English language development beyond traditional classroom instruction. The findings highlighted the importance of integrating digital platforms effectively in language learning to maximize their educational benefits.
Keywords: Digital Platforms, English Language Learning, Vocabulary Development, Mobile-Assisted Language Learning, Digital Literacy, Student Learning, Language Skills Development